ASPEK IBU DAN ASPEK SANITASI TERHADAP KEJADIAN STUNTING - Kamaruddin, Mustamir; Kaliky, M. Fadly; Afriza, Renita; Tunny, Rahma (Ensiklopedia of Journal, 2025)
Abstract: Stunting is a condition in which the growth and development of a toddler is impaired due to long-term malnutrition, which causes the child's height to be shorter than other children of the same age. Based on data tracking of stunting cases in Jambi Province, it is known that one of the districts in the top 5 highest incidence of stunting is East Tanjung Jabung District. According to sub-districts in East Tanjung Jabung Regency, the Simpang Pandan Health Center working area has the highest incidence of stunting. The purpose of the study was to determine the maternal and sanitation aspects of the incidence of stunting. The research design used in this study was cross sectional. The research was conducted in the Simpang Pandan Health Center Working Area. The research was conducted in November 2023. The population is mothers who have children aged 0-59 months in the Simpang Pandan Health Center area, totaling 1176 mothers. The sample amounted to 73 people. The sampling technique used Stratified Random Sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed a relationship between maternal knowledge (p value: 0.000) and latrine ownership (p value: 0.028) to the incidence of stunting. It is recommended to the Puskesmas to increase the knowledge of mothers and also other communities about stunting, it is hoped that the Puskesmas can increase public knowledge through preventive actions and health promotion to the community and conduct counseling to cadres in each village.Keywords: Latrines, Knowledge, Stunting